К вопросу о хаотической динамике нелинейных дискретных систем - Мандзина, В. И.; Наумейко, И. В.; Сова, А. В. (ХНУРЭ, 2018)
Some generalizations of the known discrete maps of "logistical" type are considered. It was historically developed range for research in the dynamics of nonlinear systems that describe biological, ecological, human-machine and other determined objects with complex, chaotic dynamics of their behavior.
Keywords: хаотическая динамика; нелинейная дискретная система